2005
DOI: 10.1016/j.jacc.2004.12.081
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up of the Argentine Randomized Trial of Coronary Angioplasty With Stenting Versus Coronary Bypass Surgery in Patients With Multiple Vessel Disease (ERACI II)

Abstract: At five years of follow-up, in the ERACI II study, there were no survival benefits from any revascularization procedure; however patients initially treated with CABG had better freedom from repeat revascularization procedures and from MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(60 citation statements)
references
References 31 publications
4
50
2
4
Order By: Relevance
“…21 Significant increases in repeat revascularization were observed within 1 year after the index procedure. 10,11 The rate of repeat revascularization in the LM PCI subgroup at 5 years (26.7%) is consistent with other published randomized trials and registries comparing PCI-and CABG-treated LM patients (15.7-28.4% 2,3,[14][15][16][17][18][19] ) but was higher in the CABG LM cohort (15.5%) compared with these studies (3.2-8.4%). 2,3,[14][15][16][17][18][19] In the patient population analyzed, the increased likelihood of repeat revascularization with PCI is a tradeoff; CABG has an increased stroke rate.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…21 Significant increases in repeat revascularization were observed within 1 year after the index procedure. 10,11 The rate of repeat revascularization in the LM PCI subgroup at 5 years (26.7%) is consistent with other published randomized trials and registries comparing PCI-and CABG-treated LM patients (15.7-28.4% 2,3,[14][15][16][17][18][19] ) but was higher in the CABG LM cohort (15.5%) compared with these studies (3.2-8.4%). 2,3,[14][15][16][17][18][19] In the patient population analyzed, the increased likelihood of repeat revascularization with PCI is a tradeoff; CABG has an increased stroke rate.…”
Section: Discussionsupporting
confidence: 87%
“…10,13 However, consistent with other randomized trials and nonrandomized registries of LM patients, mortality was similar in both treatment groups at 5 years. 1,3,[14][15][16][17][18][19] Only 1 propensity matched registry found increased mortality in LM patients treated with drug-eluting stents compared with CABG. 2 Procedure-related stroke is a serious and well-known complication after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, the subsequent trials in the era of drug-eluting stents (DES), in which mostly high-risk patients with diabetes mellitus or triple-vessel CAD were enrolled, have demonstrated significantly lower mortality after CABG compared with PCI. [10][11][12][13] We also have reported the better long-term outcomes in terms of all-cause death and myocardial infarction (MI) after CABG than after PCI in the all-comer CREDO-Kyoto (Coronary Revascularization Demonstrating Outcome Study in Kyoto) registry Cohort-1 and Cohort-2 in the era of BMS and DES, respectively.…”
mentioning
confidence: 99%
“…In general, these studies have demonstrated similar short-and long-term mortality with either procedure (with the exception of diabetic patients) but substantial advantages of CABG in terms of angina relief and the need for subsequent revascularization procedures. [2][3][4][5][6][7][8] Economic evaluations performed in both the balloon angioplasty and bare metal stent eras have consistently demonstrated early cost savings with PCI but similar long-term costs for the 2 strategies. 7,9,10 Clinical Perspective on p 1157…”
mentioning
confidence: 99%